Viabilidade do tratamento de água residuária sintética têxtil em reator aeróbio de leito fixo - Rodrigues, Kelly; Vidal, Carla Bastos; Aguiar Barbosa, Barbara Chaves; Pessoa-Wanderley, Carlos Ronald; Silveira Duarte, Iolanda Cristina [UNESP]; Marinho, Gloria (Assoc Brasileira Engenharia Sanitaria Ambiental, 2010)
A continuous flow reactor, inoculated with Aspergillus niger AN400, with total volume of 5 L was operated at 29 degrees C, with eight hours of retention hydraulic time and 150 L.h(-1) of air flow rate in order to remove 25 mg.L(-1) of Congo Red dye from a synthetic wastewater. The feeding of the reactor, inoculated with Aspergillus niger AN400, was done in two phases: Phase I, with 0,5 g/L of saccharose and Phase II, with no saccharose. In Phase I, it was possible to verify efficiencies of organic matter and color (mg Pt.L(-1)) removal of 80 +/- 16% and 82 +/- 10%, respectively. In Phase II, the efficiency of organic matter removal was 75 +/- 13% and color removal was 89 +/- 7%. The higher removals of nutrients were achieved by the reactor in Phase I with 25% to ammonia, 90% to nitrite, 93% to nitrate and 21% to phosphorus. Apparently, the presence of saccharose improved the removal of the nutrients.
Viability of the synthetic textile wastewater treatment in a fixed-bed aerobic reactor
Keywords: Aspergillus niger AN400; Continuous flow; Nutrients removal; Congo red